Enhancing Feed Efficiency and Growth in Early-Fattening Hanwoo Steers Through High-Energy Concentrate Feeding - Emmanuel Onche; Hyunjin Cho; Andrian Deguinion Rangandang; Namkyu Kang; Suheon Kim; Hongdae Kim; Seongwon Seo (Animals)
Adequate but not excessive dietary energy supply is crucial for growth and productivity in cattle. This study aimed to evaluate the effects of three incremental changes in metabolizable energy (ME) levels in concentrate mixes, i.e., low (LEC, 10.4 MJ/kg DM), medium (MEC, 10.8 MJ/kg DM), and high (HEC, 11.0 MJ/kg DM), on growth performance and comprehensive physiological parameters in Hanwoo steers. Thirty steers, averaging 499 ± 38.0 kg, were randomly allocated to one of the treatments. Each steer received up to 8 kg of concentrate mix, with ad libitum access to tall fescue. Body weights were measured every four weeks. In week 12, rumen samples were collected, followed by fecal and blood samples. The HEC group exhibited a 16.5% higher average daily gain compared to the other groups (p = 0.035). Forage and total dry matter (DMI) were 46% and 12% lower in the HEC group (p < 0.001). Fiber digestibility increased with energy content (p < 0.05). Total volatile fatty acid and the acetate-to-propionate ratio decreased in the HEC group (p < 0.001), while blood creatinine concentration increased (p < 0.01). In conclusion, feeding Hanwoo steers with a high-energy concentrate mix (up to 11.0 MJ ME/kg DM) improved growth and feed efficiency without compromising rumen health.